136k views
3 votes
Not a graded or timed assessment. Need help, thank you. :)

Not a graded or timed assessment. Need help, thank you. :)-example-1
User Eddys
by
5.8k points

1 Answer

0 votes

We are given the following division problem


(m^8-1)/(m-1)

We need to factor out the numerator first


m^8-1=(m^4)^2-1^2

Apply the difference of squares formula


(m^4)^2-1^2=(m^4+1)(m^4-1)

Again, factor out the term on the right side


m^4-1=(m^2)^2-1^2

Apply the difference of squares formula


(m^2)^2-1^2=(m^2+1)(m^2-1)

Again, factor out the term on the right side


m^2-1=(m)^2-1^2

Apply the difference of squares formula


(m)^2-1^2=(m+1)(m-1)_{}

Finally, the expression becomes


(m^8-1)/(m-1)=((m^4+1)(m^2+1)(m+1)(m-1))/(m-1)

(m-1) cancels out


(m^8-1)/(m-1)=(m^4+1)(m^2+1)(m+1)

Therefore, the quotient is


(m^4+1)(m^2+1)(m+1)

Or in simplified form


m^7+m^6+m^5+m^4+m^3+m^2+m+1

User Thomius
by
5.0k points